High Dose Ilaprazole/Amoxicillin as First-Line Regimen for Helicobacter pylori Infection in Korea - WonGun Kwack; YunJeong Lim; ChiYeon Lim; David Y. Graham (Gastroenterology Research and Practice)
Objective. The eradication rate of Helicobacter pylori (H. pylori) following standard triple therapy has declined over the past few decades. This study has determined whether high dose dual therapy (PPI and amoxicillin) is adequate for eradicating H. pylori in Korea. Methods. This was an open-labeled study of H. pylori infected treatment-naive patients. Subjects received dual therapy for 14 days: ilaprazole 40 mg tablets given twice a day and amoxicillin 750 mg tablets given 4 times a day. At the end of the therapy, the subjects visited the clinic to confirm compliance and monitor for any side effects. Subjects visited again after 4–6 weeks to confirm H. pylori status through a urea breath test. Results. The cure rate of H. pylori was 79.3% (23 of 29) (95% confidence interval: 61.6–90.2) in the intention-to-treat analysis and 82.1% (23 of 28) in the per-protocol analysis. Compliance rates were high (96.6%) and side effects were minimal and tolerable. Conclusion. A high dose of ilaprazole + amoxicillin was ineffective as the first-line therapy for eradicating H. pylori in Korea. Future studies should focus on intragastric pH measurements and assess amoxicillin resistance.